Growth, physiological and biochemical processes of water stressed fig (Ficus carica l.) plant influenced by anti-transpirant- brassinolide and carbon dioxide enrichment - Zulkarnaini, Zulias Mardinata (2020)
Fig (Ficus carica L.) belongs to the Moraceae family. It was a bush or small tree, moderate in size, deciduous with broad, ovate, 3 to 5-lobed leaves, contain copious milky latex and it was a new plant introduced in Malaysia. Brassinolide (BL) was a plant hormone which had biological effects on plant growth and development. While anti-transpirant containing magnesium (Mg) and calcium (Ca) as a main component was developed to increase photosynthesis and plant growth. Water stress (WS) adversely impacts many aspects of the physiology of plants, especially photosynthetic capacity. If the stress was prolonged, plant growth and productivity were severely diminished. In some other conditions, plants with high carbon dioxide (CO2) concentration grew better than plants grown under ambient air conditions. The response of plant growth to CO2 enrichment depends on the level of concentration, duration of CO2 enrichment, nutrient availability, temperature, irradiance, water, and varieties. Little information on exogenous application of BL, anti-transpirant, elevated CO2, and combination of them with WS on growth, physiological changes, and biochemical responses of fig plants. Thus, the aim of this study was (i) to investigate the effect of different concentration of exogenous application of BL on growth and physiological changes of fig var. Improved Brown Turkey (IBT) and Masui Dauphine (MD), (ii) to determine the effect antitranspirant on growth and physiological changes under optimized BL concentration and best respond fig variety, (iii) to study the possible role of exogenously applied anti-transpirant in alleviating the detrimental effects of drought in fig under optimization of BL grown under a greenhouse and (iv) to study the effect short-term elevated CO2 and water stress on biochemical responses and leaf gas exchange of fig under optimized BL concentration. Fig plant was propagated using cuttings were transferred into mixed soil 3:2:1 (3 topsoil: 2 organic matters:1 sand). In Exp. 1, two different fig varieties (V) (IBT and MD) were sprayed into four levels (0, 50, 100, and 200 ml L-1) of BL concentration. Different varieties of fig were considered as a main plot and BL concentrations (B) as a subplot. The experiment was arranged as a Split Plot Randomized Complete Block Design (SRCBD) with 4 replications (3 plants/rep). In Exp. 2, the plants were treated with four different concentrations (0, 2, 2.5, and 3 kg ha-1) of anti-transpirant rate under optimized BL concentration using the best response of fig variety from exp. 1. The experiment was laid out as a Randomized Complete Block Design (RCBD) factorial with 3 replications (3 plants/rep). In Exp. 3, the plants were subjected to two WS levels: well-watered (WW) and water-stressed (WS). WS was defined at 100% and 25% water holding capacity, respectively. The best respond fig variety was selected and exogenously applied with optimum BL and anti-transpirant rate. The experiment was arranged as RCBD factorial with 3 replications (4 plants/rep). In Exp. 4, the plant was exogenously applied with optimum BL and subjected to two WS levels as similar as in Exp 3. The plant was placed under two different greenhouses conditions (elevated with 800 ppm CO2 and without CO2 elevated). Different greenhouses conditions were considered as main fixed effects and WS as a random effect. The experiment was arranged as Nested Design with 4 replications (4 plants/rep). Biochemical processes ([proline, malondialdehyde (MDA), protein, soluble sugar content (SSC), peroxidase (POD) and catalase (CAT) enzyme activities and starch]) and leaf gas exchanges [photosynthesis rate (A), stomatal conductance (Gs), transpiration rate (E), total chlorophyll content (T-Chl), relative chlorophyll content (CC), intercellular CO2 (Ci), vapour pressure deficit (VPD), water use efficiency (WUE) and intrinsic-WUE] data were collected at monthly basis. All the data obtained were analyzed using Statistic Analysis System (SAS) version 9.4. A significant difference in mean values was determined and analyzed using two-way ANOVA and the mean differences were compared using the Least Significant Different Test (LSD) at 5% and 1% level of significance. In exp. 1, the growth and physiological changes of the fig plants were affected by different application rates of BL and the cultivars. Total leaf area (TLA), specific leaf area (SLA), and shoot-to-root-ratio (S:R) increased with increasing concentrations of BL up to 100 ml L-1, followed by a declining trend, whereas net assimilation rate (NAR) fluctuated throughout for of study. In the 1st month after treatment (MAT), increasing the BL concentration from 50 to 100 ml L-1 caused an increase in the NAR when compared to control but there was a decrease when BL concentration was 200 ml L-1. At the 2nd MAT, by increasing the BL concentration from 50 to 200 ml L-1 had decreased the NAR. Application of BL had some effect on plant height (PH), TLA, total dry biomass (TDB), SLA, and NAR but it was not significant on the S:R. Among the varieties, IBT showed higher growth than MD at every five-weekly and monthly observation. There was a significant interaction between the BL and the variety for TLA, SLA, S:R, and NAR parameters. Additionally, only S:R parameter showed a significant effect of interaction between the BL and cultivar at 1% level of significance. Interaction between BL concentrations and fig variety was significant only at 5%. Like morphological parameters, physiological traits such as A, E, and CC have shown some differences with BL application, but the differences were not consistent and most of the changes happened only in the first or second month of observation. As levels of BL increased PH, TLA, TDB, and NAR parameters also linearly improved at 28%, 25%, 6% and 66%, respectively, higher than recorded for the control treatment. In Exp. 2, as morphological parameters, physiological traits such as A, Es, Gs, WUE, Ci, and CC have shown some differences with BL application, but the differences were not consistent and most of the changes happened only in 1st or 4th MAT. Both the anti-transpirant and BL treatments were effective in the physiological responses of fig. BL treatments (control and 200 ml L-1) were significant only at parameter chlorophyll fluorescence. Anti-transpirant concentration at 2 kg ha-1 and BL concentration at 200 ml L-1 showed higher physiological responses than the other concentrations at monthly observation. The growth stimulation was more pronounced on above-ground biomass than below-ground biomass, showing a high S:R. The increase in growth and physiology in this study might have been due to increased carboxylation rate after using the BL treatment, which enhanced carbon assimilation, channeling it to stimulate an increase in PH, TLA, and TDB. In Exp. 3, drought substantially reduced the water status on Relative Leaf Water Content (RLWC), photosynthetic pigments, and leaf gas exchange. Moreover, substantially increased in biochemical responses attributes to proline content, MDA, SSC, POD, CAT but decreased on starch and protein content. However, the exogenous application of anti-transpirant remarkably improved the gas exchange and photosynthetic pigments both under drought and WW conditions. The results indicate that the application of anti-transpirant can ameliorate the effects of WW and enhance drought resistance of fig by adjusting water loss using stomatal control. Magnesium carbonate (MgCO3) was considered to be an anti-transpirant that closes stomata and thus affects metabolic processes in leaf tissues. The anti-transpirant-induced increase in photosynthesis could be due to improvements in leaf water balance as indicated by increased water potential underwater-deficit and improved CC. Anti-transpirant application substantially enhanced the activities of enzymatic antioxidants. Furthermore, CAT activity was substantially enhanced later. This regulation of enzymatic antioxidants seems the result of anti-transpirantinduced regulation of transcription and translation, which led to the improvement in the level of SSC and enzymatic antioxidants and increment in MDA and proline content. In Exp. 4, water deficiency specifically degraded the A, Gs, E, VPD, and WUE but increased Ci and int-WUE. Furthermore, a substantial increase in biochemical responses attributes to CC, proline content, MDA, SSC, POD, CAT but decreased on starch, protein content, T-Chl, and Fv/Fm. Nevertheless, elevated CO2 concurrently increased the gas exchange and CCs both under drought and WW conditions. Underwater insufficiency, enriched CO2 conditions boosted in physiological and metabolic activities were interceded through improved protein synthesis enabling maintenance of tissue water potential and activities of antioxidant enzymes reduction the lipid peroxidation. Differences in the short-term response to CO2 enrichment may be also related to differences in the sink-source status of the whole plant depending on the developmental stages. Elevated CO2 directly and indirectly, affects many plant physiological processes and biochemical accumulation in many plants and the identification of the key adaptive mechanisms to drought stress was essential to enhance the drought resistance of plants. Application of BL, anti-transpirant, and shortterm elevated CO2 increased growth, physiological changes, and biochemical responses of fig. However, the WS condition degraded the physiological processes of fig and triggered enzyme activities more active. Whereas, BL and anti-transpirant applications can ameliorate the effects of WS and enhance drought resistance of fig by adjusting water losses using stomatal control.